KOMUNITAS RAYAP TANAH PADA EMPAT LOKASI DI JAKARTA DAN JAWA BARAT - Ginuk Sumarni; Agus Ismanto (Jurnal Penelitian Hasil Hutan, 1988)
The community of subterranean  termite in any site is influenced  by the soil condition.  In three places studied  six species of  termites  were found  namely  Macrotermes  gilvus   (Hagen),   Microtermes insperatus Kemner, M. incertoides Holmgren,  Odontotermes  grandiceps   Holmgren, Capritermes  buitenzorgi  Holmgren  and Coptotermes  havilandi  Holmgren.In the yard of National  Oceanological Institute  Jakarta  C. havilandi  was responsible for  the damage of the building.  In the yard  of Forest Product  Research and Development   Centre in Bogar four  species of termite  were observed,  while at Cibodas Botanical  Garden only  one species was found   namely  C. buitenzorgi.  The latter termite  did not seem to cause to the building.